The use of patient-generated health data in the management of low anterior resection syndrome: a qualitative study - Monton, Olivia; Smith, Allister; Sabboobeh, Sarah; Demian, Marie; Cornish, Julie; Wexner, Steven D.; Christensen, Peter; Ghuman, Amandeep; Bordeianou, Liliana G.; Keane, Celia; Husain, Syed; Gasior, Alessandra; et al. (Frontiers in Surgery, 2024)
BackgroundThe cornerstone of low anterior resection syndrome (LARS) treatment is self-management, which requires patient engagement. Colorectal surgeons and nurses may use patient-generated health data (PGHD) to help guide patients in their use of self-management strategies for LARS. However, the perspectives of LARS experts on the use of PGHD remain largely unexplored. The objective of this study was to explore the perspectives and experiences of LARS experts regarding the use of PGHD in the management of LARS.MethodsWe utilized purposive snowball sampling to identify international LARS experts, including surgeons, nurses, and LARS researchers with knowledge and expertise in LARS. We conducted individual semi-structured interviews with these experts between August 2022 and February 2024. We performed thematic analysis using the framework method to identify domains and associated themes.ResultsOur sample included 16 LARS experts from five countries. Thematic analysis identified four domains and associated themes. The domains included: data collection practices, data review practices, perceived usefulness, and future directions. Within the data collection practices domain, we found that most experts asked LARS patients to collect some form of PGHD, including bowel diaries, patient-reported outcome measures, or both. Within the data review practices domain, we found that both surgeons and nurses reviewed PGHD. Most participants described finding it difficult to interpret the data and identified time constraints, legibility, and completeness as the most common barriers to reviewing data in clinic. In terms of perceived usefulness, data collection was felt to help clinicians understand symptoms and their impact and assist patients with self-management. The future directions domain revealed that most experts felt that a clinical tool in the form of an online app or website to support data collection and enhance data visualization would be useful. Finally, some participants saw promise in leveraging PGHD to inform the creation of automated treatment algorithms for LARS management.ConclusionsThis study highlights many gaps in the processes of patient-generated LARS data collection and review. A clinical tool including various data collection templates and data visualization prototypes could help to address these gaps. Future research will focus on incorporating the patient perspective.